Two new species of the genus Gergithus Stål (Hemiptera: Fulgoromorpha: Issidae) from China, with a redescription of G. bimaculatus Zhang and Che, and G. tessellatus Matsumura - Meng, Rui; Wang, Yinglun (Zootaxa, 2012)
Two new species, Gergithus nonomaculatus sp. nov. and G. tristriatus sp. nov., are described in this paper. In addition,Gergithus bimaculatus Zhang and Che, 2009 and G. tessellatus Matsumura, 1916 are given supplementary descriptions.A key to all the known species of Gergithus is provided. Variations of body colour and markings in some species of the genus Gergithus are discussed.